Climatic Characteristics of Al-Anbar Governorate: Evaluation through Climate Classifications and Mathematical Models (Journal of the College of Basic Education, 2026)
This study evaluates climatic drought in Al-Anbar Province using data from meteorological stations (Ramadi, Haditha, Anah, Al-Qaim, Rutba, Nukhaib) over a long time series (1990–2024). The analysis applies global climatic classifications and empirical equations, while introducing a new local index, the Alaa Shalal Drought Index (ASH-SDI), which integrates temperature, wind, rainfall, and relative humidity in a single equation calibrated with stability constant (C=1) and adjustment factor (K=0.05). Results show ASH-SDI values ranging between 0. 2– 0.4, confirming all stations fall within arid climate, with Nukhaib the driest and Al-Qaim/Haditha relatively less dry. Other indices support these findings: Gorczynski (continental, 51–55; Anah 48.8), De Martonne (3.04–4.95, arid desert), Sietzer (<65, arid), Selianinov (0.14–0.24, arid), Austin Miller (desert/arid), and Meigs (M, extremely arid). study concludes that drought in Al-Anbar is driven not only by rainfall scarcity but also by high temperatures, wind activity, and low humidity, underscoring the urgent need for adaptive water and agricultural management policies to mitigate desertification .